Political, Social, and Cultural Capital in the Chilean Political Elite, 1990-2010 - Garrido-Vergara, L (Cambridge University Press, 2020)
Although sociological research has examined the reproduction of Chile s elites, there is little empirical evidence of how different forms of capital operate among them. Using datasets for members of the Chilean political elite from 1990 to 2010, this country note examines and measures the effect of political, social, and cultural capital on the access of certain individuals to strategic positions in the political field, comparing the legislative and executive branches as represented by deputies and ministers. The empirical analysis includes logit models. © 2020 University of Miami.